Athletes ECG stress characteristics in Division II college athletes: a preliminary analysis - Cosio-Lima, L.; Adlof, L.; Simpson, J.; Crawley, A.; Lee, Y. (Journal of Science in Sport and Exercise, 2020)
Purpose:Two-thirds of sudden cardiac deaths are attributable to underlying cardiovascular conditions in young collegiate athletes. A 12-lead exercise stress test is a screening tool that can detect these abnormalities that may predispose collegiate athletes to sudden cardiac death, and can ensure athletes meet the physical demands of training and competition. The purpose of this study was to evaluate the electrocardiographic (ECG) characteristics of Division II collegiate athletes using the Seattle Criteria. Methods: Fifty two athletes (males = 26; females = 26) of various ethnicities (Caucasian = 65%, Latino/Hispanic = 20%, and African American = 15%); from soccer (27%), tennis (17%), basketball (15%), softball (14%), cross country (9%), volleyball (6%), football (6%), and swimming (6%) completed cardiovascular screening with resting and exercise 12-lead ECG analysis. ECG abnormalities and anthropometrics were compared across race, gender, and sports using an ANOVA. Chi-square analysis was used to test for differences in the frequency of ECG findings across gender, race, and sports. Results: Although sport was not a predictor for an abnormal ECG, 73% of the athletes presented with athletes` heart configuration, which was significantly higher in males than females (P = 0.02). The highest occurrence of these adaptations was observed in 100% of Latino/Hispanic athletes, compared to 75% of African American and 64% of Caucasian athletes. Conclusion: With newer and more sensitive ECG screening criteria, the prevalence of false-positive tests is declining. Future research should focus on advancing the sensitivity and specificity of ECG interpretation in more diverse athletic populations regarding race and gender. The increasing incidence of sudden cardiac death in collegiate athletes warrants future research that evaluates the impact of implementing the 12-lead ECG as a standard screening tool for collegiate athletes.